ANALISIS RANCANG BANGUN ANTENA YAGI DENGAN REFLEKTOR BOLIK SEBAGAI PENGUAT DAYA TANGKAP WIRELESS USB ADAPTER DENGAN FREKUENSI KERJA 2.4 GHZ - ., Tubagus Irfan Rianto (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
Antenna is a component that functions to receive and transmit electromagnetic waves. The better antenna quality in used the better signal received and transmitted. In this research the author will arrange and build the antenna by using bolic reflector to be able to increase the capture power of wireless USB adapter. The test done by comparing the yagi antenna using bolic reflector with the omni antenna, which is the reference antena on the wireless USB adapter. The measurement of signal strength is done with a distance of 30 meters and 100 meters. In antenna testing distance of 30 meters, then obtained the average of power received signal values (signal strength) for omni antenna that is equal to 67,3% or -66,25 dBm, link quality equal to 100%. And for yagi antenna with average bolik reflector that is signal strength is 85% or -57,5 dBm, link quality is 100%. At the antenna test the distance of 100 meters omni antenna cannot access the signal from the access point this distance is too far. At the same time yagi antenna with bolik reflector works well and can produce signal quality until it reaches average 53,1% or -73.45 dBm with 100% quality link. Â  Â  Keywords: Yagi antenna, wireless, Wireless USB Adapter, signal strength